Effect of sapphire-substrate thickness on the curvature of thick GaN films grown by hydride vapor phase epitaxy - Paskova, Tania; Becker, Linda; Böttcher, Tim; Hommel, Detlef; Paskov, Plamen; Monemar, Bo (Journal of Applied Physics, 2007)
The effect of sapphire-substrate thickness on the curvature and stress in thick hydride vapor phase epitaxial GaN films was studied by high-resolution x-ray diffraction at variable temperatures. The curvature was found to have the maximum value for comparable thicknesses of the film and the substrate, while the stress at the film surface decreases with increasing film thickness and increases with increasing substrate thickness, which is in very good agreement with the simulation results. The curvature at the growth temperature was found to be strongly influenced by the value of the intrinsic tensile strain, which is determined by the film/substrate thickness ratio.